2012
DOI: 10.1093/cid/cis029
|View full text |Cite
|
Sign up to set email alerts
|

Active Case Finding and Prevention of Tuberculosis Among a Cohort of Contacts Exposed to Infectious Tuberculosis Cases in New York City

Abstract: Contact investigation facilitates active case finding and tuberculosis prevention, even when completion rates of chemoprophylaxis are suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 17 publications
1
40
4
2
Order By: Relevance
“…Our finding supporting the beneficial effect of initiating treatment is consistent with results in the parent study. 7 Further research is necessary to evaluate the magnitude of this protective effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our finding supporting the beneficial effect of initiating treatment is consistent with results in the parent study. 7 Further research is necessary to evaluate the magnitude of this protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent NYC DOHMH study found that persons with a prior positive TST result were 30 times more likely to have active TB disease identified during contact investigation compared to contacts with negative TST results. 7 This unexpected finding demonstrated the possibility of new infection among contacts with a prior positive TST result and revealed a potential opportunity to prevent additional cases of active TB disease by identifying and treating those contacts at high risk for active TB disease.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations